2020
DOI: 10.1128/msphere.00464-20
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Synthesis of the MalS Malic Enzyme during Bacillus subtilis Spore Germination and Outgrowth and the Influence of Spore Maturation and Sporulation Conditions

Abstract: Spore-forming bacteria of the orders Bacillales and Clostridiales play a major role in food spoilage and foodborne diseases. When environmental conditions become favorable, these spores can germinate as the germinant receptors located on the spore’s inner membrane are activated via germinant binding. This leads to the formation of vegetative cells via germination and subsequent outgrowth and potential deleterious effects on foods. The present report focuses on analysis of the synthesis of the MalS (malic enzym… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…Metabolomics analysis of P. digitatum revealed that central carbon and energy metabolism were upregulated during germination of spores (Che et al, 2020). In line with previously reported works on gene expression during spore germination (Luo et al, 2020;Swarge et al, 2020), important cellular metabolic pathways including fatty acid biosynthesis and amino acid biosynthesis showed significant changes in the germinating spores in comparison with dormant spores (Figure 4 and Table 3). In the lipid fraction, there is a decrease in fatty acid synthase and trehalase activity (Table 2).…”
Section: Discussionsupporting
confidence: 83%
“…Metabolomics analysis of P. digitatum revealed that central carbon and energy metabolism were upregulated during germination of spores (Che et al, 2020). In line with previously reported works on gene expression during spore germination (Luo et al, 2020;Swarge et al, 2020), important cellular metabolic pathways including fatty acid biosynthesis and amino acid biosynthesis showed significant changes in the germinating spores in comparison with dormant spores (Figure 4 and Table 3). In the lipid fraction, there is a decrease in fatty acid synthase and trehalase activity (Table 2).…”
Section: Discussionsupporting
confidence: 83%
“…The same authors suggest that the observed increase in MalS-GFP fluorescence reflects a change in the environment of the germinating spore core -most likely partial ingress of water from the environment promoting enhanced fluorescence from existing MalS-GFP -and is not associated with de novo protein synthesis. The observation that malS mRNA sits outside the top 1,000 most abundant transcripts detected within spores, at levels indicative of being present in only a small sub-set of the population and with a copy number averaging much less than 1/spore (Nagler et al, 2016;Korza et al, 2019), further supports the conclusions reported by Swarge et al (2020b). Indeed, very recently published work conducted by the same group, this time combining an integrated transcriptomic and multi-faceted proteomic approach, permitting a hitherto unsurpassed level of resolution to these analyses in spores, robustly supports the idea that both transcription and protein synthesis start after the completion of germination (Swarge et al, 2020a).…”
Section: The Smoke Begins To Clearsupporting
confidence: 81%
“…Notably, the absence of nucleotide biosynthetic enzymes from spores and that these proteins are synthesized at various times in spore outgrowth have also recently been shown for B. subtilis spores in several proteomic studies (Swarge et al, 2018(Swarge et al, , 2020b. The latter findings were also made for amino acid biosynthetic enzymes as well.…”
Section: The Early Yearsmentioning
confidence: 61%
See 1 more Smart Citation
“…These changes result in water uptake by and expansion of the spore core such that core enzymes become active and metabolism and macromolecular biosynthesis resume. However, metabolism and macromolecular synthesis are most likely not required for complete germination (Setlow and Christie 2020 ; Swarge et al 2020a , b ). The order of CaDPA release first and then cortex PG hydrolysis is seen in germination of spores of Bacillales and some Clostridiales species, while in other Clostridiales, cortex PG hydrolysis precedes CaDPA release (Setlow et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%